The Postgraduate Community Pharmacy Education System: Commentary on the Swiss System - Amador-Fernández, Noelia; de Gabiole, Talitha Villien; Steeb, David; Berger, Jérôme (Indian Journal of Pharmaceutical Education and Research, 2024)
Postgraduate education is recognized to improve communication and clinical skills and to have a positive impact on pharmacists’ professional activities and responsibilities. The purpose of this commentary is to present the Swiss postgraduate education model. In Switzerland, since 2018, an authorization to practice independently requires completion of a Federal Specialized Postgraduate Diploma (FSPD). A motivating factor for pharmacists to complete the FSPD is to be authorized to bear more professional responsibilities and to support their career development. The FSPD has contributed to value pharmacists through training to support their role within the healthcare system. These advances have been officially recognized, for example, federal laws were revised in 2019 to allow pharmacists prescribing a certain list of medicines and a scheme was proposed to integrate community pharmacists in the National Vaccination Strategy. Negative impacts related to the training are in relation to its costs that are mostly covered by the trainee pharmacists and/or through a reduction on his/her salary.The increase in the magnitude of participants in postgraduate education since 2018 shows that an external constraint (change in the legislation) acts as a major driver. The Swiss postgraduate model which also includes the linking of clinical practice and accredited trainings through a competency framework whilst meeting the needs of the trainee pharmacists and pharmacies, may serve as example to other countries. However, the impact on participating pharmacists and on the distribution of roles and responsibilities within the community pharmacies’ teams should be evaluated.
Keywords: Community pharmacy; Postgraduate Education; Education Requirements; Competency-Based Education; Legislation; Pharmacy